Analysis Of Non-Performing Financing Factors In Sharia Savings And Loans Cooperative (KSPPS) Alfa Mar’atus Sholihah, Cirebon City - Safitri, Nanda Aisyah; Sari, Linda; Sutirwan Wahdiat, Irwan; Mardi, Mardi (Jurnal Ekuisci, 2025)
Aims. This research was conducted to identify various factors contributing to the emergence of Non-Performing Financing (NPF) in the Sharia Cooperative Alfa Mar’atus Sholihah. Methods. This study uses a descriptive, qualitative approach categorized as field research. The main data source comes from primary data collected through observations, interviews, and documentation involving the secretary and employees of the Sharia Savings and Loans Cooperative Alfa Mar’atus Sholihah. Results. The findings indicate that the factors causing NPF in the Sharia Cooperative Alfa Mar’atus Sholihah consist of internal factors, such as the financing process and the profit-sharing system, as well as external factors, such as the character of customers and economic growth. Conclusions. Based on research at KSPPS Alfa Mar’atus Sholihah, internal and external factors influence Non-Performing Financing (NPF). Internally, while the financing system is adequate with proper education and monitoring, issues arise in installment payments and unclear profit-sharing agreements. Externally, NPF is affected by member characteristics like low repayment ability and reliance on stable economic growth. To reduce NPF, the cooperative should strengthen education, monitoring, and member engagement, while staying responsive to economic changes. Implications. These findings provide insights for the management of KSPPS Alfa Mar’atus Sholihah to improve financing procedures and customer education, as well as to consider customer characteristics and economic conditions in financing management